Smallholder dairy cattle production in the northeast of Vietnam - Yaemkong, Suphawadee; Ngoc, Tuan Nguyen; Kolnathon, Panadda; Yaemkong, Sirikranda (Health Science, Science and Technology Reviews, 2018)
A survey was aimed to characterize the dairy cattle production of small scale farming in Ba Vi district, Ha Tay Province, Vietnam. Two hundred fifty purposive responders were enrolled. The majority of farmers were men (68.7%), with an average (SD) age of 43.7 (8.1) years and average farm experience was 11.9 (6.8) years. Most of them (94.0%) were family members. The average herd size was 6 (3.4), and mostly (37.8%) were milking cows, Holstein Friesian crossbred and were fed by the cut and carried grasses (92.59%) as well as all supplemented with the mineral and salt. The livestock production contributed up to 64% of farmer income in the area. Other characteristics will be described.